Comparing simultaneous versus staged resection in patients with synchronous colorectal liver metastases: case match study - Elagili, Faisal; Ozuner, Gokhan; Berber, Eren; Akyuz, Muhammet; Cem Dural, Ahmet (Elsevier, 2014)
INTRODUCTION: There is no consensus on the optimal timing of liver resection in patients with synchronous colorectal liver metastasis. METHODS: Patients undergoing hepatic resections between 2004- 2013 for synchronous colorectal liver metastases were analyzed from a prospectively maintained and institutional review board approved database. Patients who underwent simultaneous resection of a colorectal primary and hepatic metastasis in a single operation (Group I) were case-matched 1:1with patients who underwent staged operation (Group II) according to age, sex, ASA classification, size of liver lesion and number of liver lesion. RESULTS: 66 patients (33 Group I, 33 Group II) were matched from a total cohort of 106 patients with synchronous colorectal liver metastasis. The patients’ characteristics of both groups were similar. 62% were male and the mean age was 55.511 years. Blood loss and duration of surgery did not differ between simultaneous resections and staged resection (p¼0.63; p¼0.14, respectively). Perioperative complication rate were similar in both groups (P¼0.70). There was no mortality. The median number of in-hospital days during the course of treatment was 9 (4-23) days in Group I and 6 (3-17) days in Group II (p <0.001). There was no difference in 2 years disease free survival and overall survival were found between Group I and Group II ( 30% and 34%, p¼ 0.58; 67% and 62%, p¼0.86 respectively). CONCLUSIONS: Simultaneous liver resections result in similar short and long eterm outcomes as in patients undergoing sequential resections for synchronous colorectal cancer with comparable metastatic disease burden.